Poverty reduction effects of agricultural technology adoption: the case of improved cassava varieties in Nigeria - Assfaw Wossen, Tesfamicheal; Alene, A.; Abdoulaye, Tahirou; Feleke, S.; Rabbi, Ismail Y.; Manyong, Victor M. (Wiley, 2018)
We use DNA‐fingerprinting to estimate the poverty reduction effect of adoption of improved cassava varieties in Nigeria. We estimate the counterfactual household income distribution of cassava producers by combining farm‐level treatment effects with a market‐level model. Our results suggest that adoption of improved cassava varieties has led to a 4.6 percentage point reduction in poverty, though this is sensitive to the measurement of adoption status. Therefore, accurate measurement of adoption is crucial for a more credible estimate of the poverty reduction effect of adoption. Our analysis also suggests that farmers who are more likely to be adopters are also likely to face higher structural costs. Addressing structural barriers that make improved technologies less profitable for the poor would therefore be important to increase the poverty reduction effect of improved cassava varieties.